Evolução da urbanização e seu efeito no escoamento superficial na bacia do riacho Reginaldo, Maceió-AL - Silva Júnior, Rubem Izidro da (2009)
The city of Maceió has gone through an intense urbanization process, changing from c. 163000 inhabitants in 1950 to c. 798 000 inhabitants in 2000. As a consequence of urbanization, impacts on urban drainage are evident, due to soil impermeabilization. Reginaldo creek watershed, which has a drainage area of 27 km², has been impaired by stormwater drainage effects, characterized by frequent floods in several places. Recently, it has been observed an increase in frequency and magnitude of floods, due to runoff augmentation. This master thesis aims at identifying and characterizing Reginaldo creek watershed’s urbanization temporal evolution and its impacts on runoff generation. Soil use and occupancy evolution within the basin was assessed via the estimation of the CN parameter applied in the SCS model and its impacts on runoff were assessed via rainfallrunoff simulation using the IPH-S1 model. Data were acquired in field trips, public institutions related to stormwater drainage, aerial imagery from 1960, 1980 and 2004 and from a city map. It was found that the basin has gone through an intensive process of native vegetation elimination, with significant occupation of the basin lower areas, expanding to upper areas. Occupation of riverbanks has occurred similarly to what occurs in its main. No concern has been given to the water cycle, when selecting areas to occupy and there are still areas without sewer systems, affecting water quality in streams. CN estimations resulted in a significant increase, with direct consequences in runoff. The rainfall-runoff simulations with 2 years design storm showed that discharges increased from 32 m³ / s in the 1960 scenario to 70 m³ / s in 2004 scenario. Direct implications in the runoff are greater with existing urbanization patterns (small lots and complete impermeabilization) and watershed’s physical characteristics (steep slopes and clay soil).